An indoleacetate‐CoA ligase and a phenylsuccinyl‐CoA transferase involved in anaerobic metabolism of auxin. (26th May 2016) - Schühle, Karola; Nies, Jonas; Heider, Johann
Summary: The plant hormone auxin (indoleacetate) is anaerobically degraded by the Betaproteobacterium Aromatoleum aromaticum . We report here on a CoA ligase (IaaB) and a CoA‐transferase (IaaL) which are encoded in the apparent substrate‐induced iaa operon containing genes for indoleacetate degradation. IaaB is a highly specific indoleacetate‐CoA ligase which activates indoleacetate to the CoA‐thioester immediately after uptake into the cytoplasm. This enzyme only activates indoleacetate and some closely related compounds such as naphthylacetate, phenylacetate and indolepropionate, and is inhibited by high concentrations of substrates, and by the synthetic auxin compound 2, 4‐dichlorophenoxyacetate, which does not serve as substrate. IaaL is a CoA‐transferase recognizing several C4‐dicarboxylic acids, such as succinate, phenylsuccinate or benzylsuccinate and their CoA‐thioesters, but only few monocarboxylic acids and no C3‐dicarboxylic acids such as benzylmalonate. The enzyme shows no stereospecific discrimation of the benzylsuccinate enantiomers. Moreover, benzylsuccinate is regiospecifically activated to 2‐benzylsuccinyl‐CoA, whereas phenylsuccinate is converted to an equal mixture of both regioisomers (2‐ and 3‐phenylsuccinyl‐CoA). The identification of these two enzymes allows us to set up a modified version of the metabolic pathway of anaerobic indoleacetate degradation and to investigate the sequences databases for the occurrence and distribution of this pathway in other microorgansisms.